Therapy of episodic ataxias: case report and review of the literature - Daniele Orsucci; Laura Maria Raglione; Monica Mazzoni; Marco Vista (BioExcel Publishing Ltd, 2019)
Episodic ataxias (EAs) are characterized by recurrent, discrete episodes of vertigo and ataxia. EA1 and EA2 are the two most common forms. In the interictal interval, myokymia is typically present in EA1, whereas EA2 patients present with interictal nystagmus. Specific pharmacological therapies are available for EA1 and especially EA2. We briefly discuss the case of an Italian young man with EA2, with a novel de novo CACNA1A mutation, who in our opinion is particularly illustrative for introducing the therapeutic approach. Acetazolamide could fully suppress EA episodes in our patient. We also provide a perspective review of the topic. 4-Aminopyridine is another valid treatment option. For EA1 (and for rarer EAs), the therapeutic possibilities are more limited. Carbamazepine is probably the treatment of choice for EA1, but the optimal treatment plan is unknown. A better understanding of the molecular processes involved in the mediation of EAs will lead to more specific and efficacious therapies for this still elusive group of disorders.